Age in love : Shakespeare and the Elizabethan court - Vanhoutte, Jacqueline, 1968- (Lincoln, Nebraska : University of Nebraska Press, 2019)
"Age in Love contributes to the ongoing debate about the emergence of a Tudor public sphere, building on the current interest in premodern constructions of aging and ultimately demonstrating that the Elizabethan court shaped Shakespeare's plays in unexpected and previously undocumented ways"--
Endymion at the aging court -- Falstaff among the minions of the moon -- Remembering old boys in Twelfth night -- Antony.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on May 02, 2019).
JSTOR
Keywords: Shakespeare, William, -- 1564-1616 -- Political and social views; Shakespeare, William, -- 1564-1616 -- Characters -- Queens; Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Relations with courts and courtiers; Elizabeth -- I, -- Queen of England, -- 1533-1603 -- Relations with courts and courtiers; Shakespeare, William, -- 1564-1616 -- Characters -- Queens; Shakespeare, William, -- 1564-1616 -- Political and social views; Elizabeth -- I, -- Queen of England, -- 1533-1603; Shakespeare, William, -- 1564-1616; English literature -- Early modern, 1500-1700 -- History and criticism; Older men in literature; Courts and courtiers in literature; Great Britain -- Court and courtiers -- History -- 16th century; Hommes âgés dans la littérature.; Cours et courtisans dans la littérature.; DRAMA -- English, Irish, Scottish, Welsh; LITERARY CRITICISM -- Renaissance; Courts and courtiers; Courts and courtiers in literature; English literature -- Early modern; Older men in literature; Political and social views; Queens in literature; Relations with courts and courtiers; Great Britain; 1500-1700; Criticism, interpretation, etc; History